Paternal alcohol exposures program intergenerational hormetic effects on offspring fetoplacental growth - Thomas, Kara N.; Zimmel, Katherine N.; Basel, Alison; Roach, Alexis N.; Mehta, Nicole A.; Thomas, Kelly R.; Dotson, Luke J.; Bedi, Yudhishtar S.; Golding, Michael C. (Frontiers in Cell and Developmental Biology, 2022)
Hormesis refers to graded adaptive responses to harmful environmental stimuli where low-level toxicant exposures stimulate tissue growth and responsiveness while, in contrast, higher-level exposures induce toxicity. Although the intergenerational inheritance of programmed hormetic growth responses is described in plants and insects, researchers have yet to observe this phenomenon in mammals. Using a physiologically relevant mouse model, we demonstrate that chronic preconception paternal alcohol exposures program nonlinear, dose-dependent changes in offspring fetoplacental growth. Our studies identify an inverse j-shaped curve with a threshold of 2.4 g/Kg per day; below this threshold, paternal ethanol exposures induce programmed increases in placental growth, while doses exceeding this point yield comparative decreases in placental growth. In male offspring, higher paternal exposures induce dose-dependent increases in the placental labyrinth layer but do not impact fetal growth. In contrast, the placental hypertrophy induced by low-level paternal ethanol exposures associate with increased offspring crown-rump length, particularly in male offspring. Finally, alterations in placental physiology correlate with disruptions in both mitochondrial-encoded and imprinted gene expression. Understanding the influence of ethanol on the paternally-inherited epigenetic program and downstream hormetic responses in offspring growth may help explain the enormous variation observed in fetal alcohol spectrum disorder (FASD) phenotypes and incidence.